From Companies to Markets : Global Developments in Corporate Governance - International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
Good corporate governance is a basic element for healthy companies and a key to sustainable private sector development. Strong governance fundamentals contribute to better management and more effective boards, leading to enhanced operational efficiency, reduced risk, improved decision making, and increased valuations, among other business benefits. This publication represents a unique collaborative effort to assess the state of corporate governance around the world in the wake of the 2008 global financial crisis. It draws on the expertise of the IFC Corporate Governance Private Sector Advisory Group and other practitioners in this important field, providing a fascinating and detailed accounting of the range of changes that have taken place in the past few years as the corporate governance agenda has been elevated. The report highlights notable improvements in board practices, control environment, shareholder protection, and transparency and disclosure. It also points to progress on more effective application, monitoring, and enforcement of corporate governance codes. Importantly, the publication identifies future directions where more work is needed, such as increased commitment at the national level to prioritize the corporate governance agenda. Specifically, Part A discusses developments from global or regional groups involved in corporate governance. Part B addresses developments in corporate governance practice, and Part C looks at developments in corporate governance codes and standards.